INTERPRETASI AKUIFER DANGKAL DAN DALAM DENGAN MENGGUNAKAN METODE INVERS SMOOTHNESS-CONSTRAINT LEAST SQUARES DATA GEOLISTRIK KONFIGURASI SCHLUMBERGER DI PLTU TENAYAN RAYA - Aji Susoso; M Juandi; Rahmi Dewi; Usman Malik (Fakultas Teknik Universitas Pasir Pengaraian, 2019)
Research of The Interpretation of shallow and deep aquifer by using inversion methods Smoothness-Constraint Least Squares Geoelectric Data Configuration Schlumberger At Tenayan Raya electric steam power Plan has been successfully done and get result. The study was conducted with the aim to analyze and know the potential of shallow and deep aquifer reserve in the area of Tenayan Raya electric steam power Plan. One way to find out the groundwater resources is by exploring using the Schlumberger geoelectric configuration method. This geoelectric method is used to find out the condition of groundwater presence in the location of Tenayan Raya electric steam power Plan with more accurate result. The deep aquifer (water carrier) obtained with the schlumberger geolistrik and then modeled with the Smoothness-Constraint Least Squares Inversion Method which has a smaller error rate. Measurements are made on three (3) stretches in The location of Tenayan Raya electric steam power Plan. The results obtained on the measurement shows the amount of groundwater potential at the location of Tenayan Raya electric steam power Plan at a depth ranging from 17 to 130 m for shallow aquifer Ana 240 m upward for a deep aquifer. The amount of water reserve in the area of Tenayan Raya electric steam power Plan until the depth is 11.300.000 m3 for shallow aquifer Ana for deep aquifer in The Mount of 11.000.000 m3. Keywords : Aquifer, Inversion, Smoothness, Geoelectric, Schlumberger